The values of HER-2 expression in the non-muscle-invasive bladder cancer: a retrospective clinical study - Wang, Shuo; Ji, Yongpeng; Liu, Yiqiang; Du, Peng; Ma, Jinchao; Yang, Xiao; Yu, Ziyi; Yang, Yong (Frontiers in Oncology, 2023)
Purpose The purpose of this research is to evaluate the association between HER-2 expression and clinicopathological features in patients with non-muscle-invasive bladder cancer (NMIBC). Methods Between 2019 and 2022, 204 patients treated with Transurethral resection of the bladder tumor (TURBT) were included in this study. Data of pathologic T (pT) stage, grades of the tumor, age, sex, tumor size and number of the tumors were collected and compared according to the expression level of the human epidermal growth factor 2 (HER-2). ROC curve analysis was performed to assess the discriminative ability of HER-2 expression for tumors grades and pT stage. Multivariable logistic regression analysis were used to evaluate the association between HER-2 expression and tumor grades and pT stage. Results Patients were divided into low grade (110, 53.9%) and high grade groups (94, 46.1%) according to the tumor grade. Pathologic stage consisted of pTa in 166 (81.4%) and pT1 in 38 (18.6%). HER-2 expression was semi quantitatively scored to 0 in 44 (21.6%), 1 in 58 (28.4%), 2 in 91 (44.6%), and 3 in 11 (5.4%) cases. HER-2 expression was significantly associated with tumor stages and histological grades, but not with sex, tumor size or number of tumors. The AUC for combination of HER-2 expression with tumor stages and histological grades was 0.652 (p < 0.003) and 0.727 (p < 0.001), respectively. Conclusion This study demonstrated that HER-2 expression is associated with tumor stages and histological grades in NMIBC. It has diagnostic value for cystoscopic biopsy.